Pengaruh Inovasi Produk dan Citra Merek terhadap Keputusan Pembelian Smartphone Merek iPhone di Kota Bandung - Fathia Novara Litta; Budi Prasetiyo (STIKes Ibnu Sina Ajibarang, 2025)
The evolution of technology and fierce rivalry in the smartphone sector compel companies to consistently innovate and cultivate a robust brand presence to sustain their market standing. Innovation in products opens up avenues for incorporating new functionalities, improving aesthetics, and delivering enhanced value to consumers. Conversely, a favorable brand presence bolsters customer fidelity, fosters trust, and sways purchasing choices. This research seeks to evaluate both the isolated and combined effects of product innovation and brand presence on the buying choices of iPhone smartphones in Bandung. The study employs a quantitative approach with a descriptive causal framework. The participant group consists of 100 iPhone users in Bandung, identified through a non-random sampling method known as purposive sampling. Techniques for data analysis included descriptive statistics and multiple linear regression. The findings revealed that product innovation has a substantial partial influence on purchasing choices. Additionally, brand presence plays a significant role in shaping purchase decisions on its own. Collectively, product innovation and brand presence impact buying decisions in 93.9% of the cases examined, while the residual 6.1% is impacted by factors outside the scope of this research.